A Comparative Study on Performance of Public and Private Telecommunication Sectors with Reference to Wireless Services in Assam Circle - Baruah, Papori; Baruah, Rashmi R. (International Journal of Social Sciences and Management, 2015)
Indian Telecom Sector is one of the fastest growing domains compared to other sectors of development, which has received extensive investments, both by government as well as private players in the recent years. The prime purpose of this study was to compare the performance of Public and Private Telecommunication sector with reference to wireless services in Assam Telecom Circle. The paper tried to explore and understand the major similarities and differences existing between the public and private cellular service providers in terms of market penetration effectiveness, their subscribers’ base, revenue earned by them etc. in the above mentioned Circle. National and State level data of Telecom Sector was collected on a periodic basis over time. A critical evaluation had been done with the help of Applied Analytical Research, by using facts and information already available. The result showed that there were few common factors applicable to both Public and Private Telecom Sector; however significant differences in performance are there in these sectors in Assam Circle. The key findings from this study describe that visibly the Private Sector had better performance than Public Sector in terms of few parameters considered in this study, which might indicate a possible development direction for the effectiveness of Public Sector in this Circle. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 188-192 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12570